VD_FINDINFO HC / 2010 / 628 vom 3. September 2010 - VD Tribunal cantonal (2010)
ERREUR ESSENTIELLE, VICE DU CONSENTEMENT, CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE | 23 CO, 24 al. 1 ch. 2 CO, 24 al. 1 ch. 4 CO, 337 al. 1 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 46 LJT